Cloning of a grapevine Botrytis-responsive gene that has homology to the tobacco hypersensitivity-related hsr203J - Bézier, Annie (Journal of experimental botany, 2002)
A cDNA encoding a putative HSR203J-like protein (BIG8.1) was obtained from total RNA isolated from Botrytis cinerea-infected grapevine leaves using differential display and RACE techniques. Real time RT-PCR analysis confirmed that the level of mRNA corresponding to BIG8.1 increased in grapevine leaves during the infection progress by B. cinerea. No significant change in mRNA level was observed in leaves after UV exposure. This expression pattern suggests that BIG8.1 could be a HR-specific marker in grapevine like hsr203J in tobacco